Building national patient registries in Mexico: insights from the MexOMICS Consortium - Reyes-Pérez, Paula; Hernández-Ledesma, Ana Laura; Román-López, Talía V.; García-Vilchis, Brisa; Ramírez-González, Diego; Lázaro-Figueroa, Alejandra; Martinez, Domingo; Flores-Ocampo, Victor; Espinosa-Méndez, Ian M.; Tinajero-Nieto, Lizbet; Peña-Ayala, Angélica; Morelos-Figaredo, Eugenia; et al. (Frontiers in Digital Health, 2024)
To introduce MexOMICS, a Mexican Consortium focused on establishing electronic databases to collect, cross-reference, and share health-related and omics data on the Mexican population. METHODS: Since 2019, the MexOMICS Consortium has established three electronicbased registries: the Mexican Twin Registry (TwinsMX), Mexican Lupus Registry (LupusRGMX), and the Mexican Parkinson's Research Network (MEX-PD), designed and implemented using the Research Electronic Data Capture web-based application. Participants were enrolled through voluntary participation and on-site engagement with medical specialists. We also acquired DNA samples and Magnetic Resonance Imaging scans in subsets of participants. RESULTS: The registries have successfully enrolled a large number of participants from a variety of regions within Mexico: TwinsMX (n=2915), LupusRGMX (n=1761) and MEX-PD (n=750). In addition to sociodemographic, psychosocial, and clinical data, MexOMICS has collected DNA samples to study the genetic biomarkers across the three registries. Cognitive function has been assessed with the Montreal Cognitive Assessment in a subset of 376 MEX-PD participants. Furthermore, a subset of 267 twins have participated in cognitive evaluations with the Creyos platform and in MRI sessions acquiring structural, functional, and spectroscopy brain imaging; comparable evaluations are planned for LupusRGMX and MEX-PD. CONCLUSIONS: The MexOMICS registries offer a valuable repository of information concerning the potential interplay of genetic and environmental factors in health conditions among the Mexican population.